Factors related to the selection of baby massage services - Nur Zuwariah; Uliyatul Laili (Alma Ata University Press, 2022)
Background: Many factors influence parents in making the decision to do baby massage. These factors should be screened by health workers in providing counseling to mothers. So, it is hoped that the mother can choose the right facility. Objectives: The purpose of this study was to analyze what factors influence mothers in the selection of baby massage services. Methods: The research method is quantitative, with a cross sectional study. The research was conducted at PBM Nanik Sidoarjo. The population in this study were mothers who had children aged 3 - 12 months. Samples were taken using purposive sampling. Inclusion criteria in sampling are mothers who are aged 3-12 months without health problems/complications of accompanying diseases. The independent variables in this study are the factors that influence the mother, namely the socio-demographic of the community (age, occupation, education, income, and traditional baby massage culture), while the dependent variable is the selection of baby massage methods. Direct data collection using questionnaires distributed to mothers. Furthermore, the data were analyzed by chi square test. Results: The results showed that the number of respondents who chose to do baby massage to traditional birth attendants and to health facilities was the same, namely 40%. The results of the statistical analysis showed that educational and cultural factors were related to the selection of baby massage services with p-values of 0.006 and 0.003 <0.05. While the factors of age, occupation and income did not show significant results with a p value > 0.05. Conclusions: So it can be concluded that the factors that influence the selection of baby massage services are educational and cultural factors.